The Effects of Strategic Planning in Outsourcing Relationships among Large Scale Food Processors in Kenya - Sanita Mulewa, Susan Mary; Mugambi Mwirigi, Dr. Fred; Hood Ahmed, Dr. Anwar (IJRDO - Journal of Business Management, 2017)
The purpose of this study was to establish the effects of strategic planning as a strategic management practice in outsourcing relationships among large sale food processors in Kenya. Stratified random sampling was applied in the selection of the large scale food processing in Kenya. Through the stratified random sampling, the study respondents were 123 large scale food processing firms in Kenya. The study used questionnaires for data collection. From 123 questionnaires distributed, data was then collected, coded and analysed. From the analysis, the study found a weak positive linear relationship between strategic planning and outsourcing relationships since strategic planning (r =0.476) whose significant value was 0.000 being less than 5% as the level of significance. It thus concluded that the effects of strategic planning in outsourcing relationships among the large scale food processing firms in Kenya is equally important